2015
DOI: 10.1111/bph.13154
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ventricular pacing‐induced postconditioning attenuates reperfusion injury: effects on peroxynitrite, RISK and SAFE pathways

Abstract: Background and PurposeRapid ventricular pacing (RVP) applied before an index ischaemia has anti‐ischaemic effects. Here, we investigated whether RVP applied after index ischaemia attenuates reperfusion injury and whether peroxynitrite, reperfusion injury salvage kinase (RISK) and survival activating factor enhancement (SAFE) pathways as well as haem oxygenase 1 (HO1) are involved in the mechanism of RVP‐induced postconditioning.Experimental ApproachLangendorff perfused rat hearts were subjected to 30 min regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…Tissue lipid accumulation is often associated with increased nitro-oxidative stress in various organs, therefore we have also investigated the effect of isolated hypercholesterolemia on nitro-oxidative stress in the liver. Our findings showing elevated hepatic nitro-oxidative stress due to isolated hypercholesterolemia is in line with our own observations made previously in the heart [ 32 , 37 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tissue lipid accumulation is often associated with increased nitro-oxidative stress in various organs, therefore we have also investigated the effect of isolated hypercholesterolemia on nitro-oxidative stress in the liver. Our findings showing elevated hepatic nitro-oxidative stress due to isolated hypercholesterolemia is in line with our own observations made previously in the heart [ 32 , 37 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…To further characterize hepatic damage induced by isolated hypercholesterolemia 3-nitrotyrosine level was measured in liver samples as a marker of tissue nitro-oxidative stress using ELISA (Cayman Chemical, Ann Arbor, MI, USA) as described previously [ 38 , 41 , 42 ]. Briefly, homogenates were incubated overnight with nitrotyrosine acetylcholinesterase tracer and anti-nitrotyrosine rabbit IgG in microplates pre-coated with mouse anti-rabbit IgG.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, PPC induced a remarkable reduction in the CK and LDH levels. Although evaluations of hemodynamics have seldom been conducted, the protective effects of PPC were reported by us and other researchers [1,2,30,34]. However, the pathways involved in PPC-mediated protection and the interaction between PPC and body homeostasis have not been completely elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…Here we show that PPC induced cardiac protection also involves enhanced activation of ERK1/2 and Akt (Fig 5). In contrast however Pipicz and his group have demonstrated that rapid ventricular pacing does not induce ERK1/2 activation [52]. The reason behind this discrepancy is however not clear.…”
Section: Discussionmentioning
confidence: 97%